GENERAL CHARACTERISTICS AND TYPES OF OBJECTS OF CRIMINOLOGICAL SAFETY (Law and Safety, 2018)
The general characteristics and types of objects of criminological safety have been researched. It has been emphasized that criminological safety as one of the components of public safety is one of the obligatory attributes that ensure the normal functioning of a democratic state. It has been proved that ensuring the criminological safety is the system of measures implemented by state and other agencies, organizations and institutions as well as by individual citizens in order to protect the important interests of individuals, society and the state. Law enforcement agencies play a key role in implementing these measures, although the priority in this work should be given to the family, school and community organizations.It has been substantiated that the main objective of ensuring the criminological safety of society, individuals and the state is the timely detection of criminological threats, their neutralization and reflection. The nature and type of a threat affect the choice of measures to ensure the criminological safety, determine the directions of ensuring safety, facilitate to detect possible objects of criminal encroachments. Their specification facilitates the coordination of activities of various state and public structures.The content and essence of public safety have been defined. It has been noted that the criminological safety within the system of public safety plays a double role. The characteristics of the main objects of the criminological safety have been provided. It has been emphasized that the objects of the criminological security in general are phenomena, processes and relations, the protection of which is the objective and the main content of the criminological safety policy.It has been established that the criminological safety is one of the most important types of public safety, it is part of the structure of its system and plays an important role in ensuring safety from natural and man-made threats for possible provoking of man-made and environmental threats by a person, and from social sources of threats of a criminal nature. Its main objects are individuals, society and the state.
Keywords: safety, criminological safety, objects of criminological safety, public safety, components of public safety.